Racism and health care: Experiences of Latinx immigrant women in NYC during COVID-19 - Monika Damle; Heather Wurtz; Goleen Samari (Elsevier, 2022)
The COVID-19 pandemic has disproportionately affected minoritized racial groups, especially Latinx immigrants, evidenced by the high rates of COVID-19 infections, hospitalizations, and deaths among this population. With increasing xenophobia and anti-immigrant sentiment in parallel to the pandemic, it is critical to understand the perspectives of Latinx populations. This study explores Latinx immigrant women's perceptions of racism and xenophobia in their health care experiences in New York City (NYC) during the COVID-19 pandemic and, further, seeks to understand the role of perceived discrimination in health care settings and on health care access. Data were analyzed using a constant comparative method of analysis from twenty-one in-depth interviews conducted with foreign-born women in the five boroughs of New York City from diverse countries across Latin America. Four central themes emerged including: structural inequalities, discriminatory health care experiences, victimization in public institutions, and overcoming discrimination in health care settings. Latinx immigrant women described the ways in which perceptions and experiences of discrimination shaped their capacity to address health-related needs during the COVID-19 pandemic. This study provides evidence to a growing body of literature suggesting that structural racism and xenophobia and perceptions of anti-immigrant discrimination, including resulting structural inequalities, may have a negative effect on individuals' ability to access and engage the health care system, resulting in avoidance of health care services - a critical need during a global pandemic. Scholars, policymakers, and practitioners alike should be mindful of how racism and xenophobia shape Latinx immigrant communities' engagement with the health care system.